Family Archive Storage System For Effective Retrieval Of Archives Of Residents Of Dinoyo Malang Village - Tatiana Kristianingsih; Farika Nikmah; Evi Suwarni (Journal of Economics and Business UBS, 2023)
Currently, there are still many family archive treatments that have not been handled properly. There are still difficulties in finding archives when they need them for administrative needs. Each member faces various problems in the management of archives, due to lack of awareness. Therefore, family archives that are managed systematically will provide convenience in solving problems faced quickly and effectively Family archive management is needed by every family in storing and handling family records that are considered to contain important information. There are many archive storage systems ranging from storage systems based on subject, name, date, region and number. This study aims to find out and analyze the appropriate family archive storage system to measure how effective it is for retrieval of archives that have been stored, the research method used is descriptive research with a qualitative approach. The data collection technique used is through informant interviews and documentation. The results showed that as many as 42 respondents had done a good archiving for their family archives even though it was not systematic in accordance with the existing archive storage system. The remaining 8 respondents still did not do a good filing for their family documents. So that for the process of retrieving the archives needed, the average respondent, especially those who do not file family documents properly, find it difficult to find the documents needed. From this research, it can be concluded that the importance of managing family archives properly to facilitate the rediscovery of needed archives and most importantly also maintain vital archives that have very important use value so as not to be damaged